Parenting Practices and Pupils’ Academic Achievement in Primary School of Dawakin Kudu Local Government Area, Kano State of Nigeria - Hassan, Muhammad; Mohammed, Auwalu Inusa (NIU Journal of Humanities, 2017)
This study was carried out in 14 primary schools of Dawakin kudu Local Government Area in the Kano State of Nigeria, with the aim finding out if there is there a relationship between parenting practices and primary pupils’ academic achievement in Dawakin kudu local government area.  A total of 300 primary Four and Primary Five pupils selected randomly participated in the study which took a cross-sectional survey design using quantitative approach. The learners’ academic achievement was based on end of term, December 2016 Results in eight subjects namely; English, Mathematics, Primary Science, Social Studies, Writing, Hausa (a local language), Physical Education, as well as Art and Craft.  The finding indicates that there is a significant relationship between parenting practices and primary school pupils’ academic achievement. The conclusion made was that the academic achievement of the learners depends on many factors. Parenting practices are among those factors. The higher the parenting practices are rightly used or applied, the higher the possibility of the learners getting good results, and vice-versa. The study also recommended that parents  should give adequate time for their children to get highly involved with them, monitor them , and communicate goals, values and aspirations to them; there is need for the parents in rural areas to try their best to close that gap so that all parents wherever they are can properly fulfill their parental roles towards their children; children should also be guided by the teachers to stop perceiving Mathematics as a hard subject, yet actually it is not different from other subjects; and there is need for parents to get involved more in their children’s education, highly monitor their children and highly communicate to them the goals, values and aspirations. Keywords: parenting practices, primary pupils, and academic achievement